Defects in castings during high‑pressure casting and measures to prevent their formation - V. I. Chechukha; M. A. Sadokha (Литьë и металлургия, 2024)
The article presents a list of defects in castings formed during high‑pressure casting. It has been established that each cause that creates conditions for the formation of specific defects in castings is interconnected with the incorrect setting of specific casting technological parameters. Measures to prevent the formation of defects have been determined depending on the casting technological parameters, operating modes of the mold, application of release lubricant, and alloy preparation. To ensure high quality of produced castings, it is necessary to minimize the influence of the human factor during the casting process. This can be achieved by using modern foundry equipment, high‑quality charge and auxiliary materials, and by applying automated high‑pressure casting complexes in serial and mass production.